1. Solve for   x   and check.

2(5x -7) - (2x - 5) = 3(2x - 1)

First, remove parentheses.

10x - 14 - 2x + 5 = 6x - 3

Combine like terms

8x - 9 = 6x - 3

Transpose   x   terms to one side and numbers to the other.

8x - 6x = 9 - 3

Combine like terms.

2x = 6

Divide both sides by the coefficient of the unknown

x = 6/2 = 3

Check

Copy down the original equation

2(5x -7) - (2x - 5) = 3(2x - 1)

except copy down the solution in parentheses wherever you see the unknown.

2(5(3) - 7) - (2(3) - 5) = 3(2(3) - 1)

This gives us an order of operations problem. Do what's inside the parentheses first. Inside each parentheses is a multiplication and a subtraction problem. Do the multiplication first, and copy down the rest of the problem.

2(15 - 7) - (6 - 5) = 3(6 - 1)

Next, subtract inside the parentheses.

2(8) - (1) = 3(5)

Do the multiplications first.

16 - 1 = 15

Subtract.

15 = 15

and it checks.

Return to test